Can erythrocytes release biologically active NO?. Issue 1 (December 2016) - Benz, Peter; Fleming, Ingrid
Abstract Under physiological conditions, endothelial cells and the endothelial nitric oxide (NO) synthase (eNOS) are the main source of NO in the cardiovascular system. However, several other cell types have also been implicated in the NO-dependent regulation of cell function, including erythrocytes. NO derived from red blood cells has been proposed to regulate erythrocyte membrane fluidity, inhibit platelet activation and induce vasodilation in hypoxic areas, but these proposals are highly controversial. In the current issue ofCell Communication and Signaling, an elegant study by Gambaryan et al., assayed NO production by erythrocytes by monitoring the activation of the platelet intracellular NO receptor, soluble guanylyl cyclase, and its downstream kinase protein kinase G. After systematically testing different combinations of erythrocyte/platelet suspensions, the authors found no evidence for platelet soluble guanylyl cyclase/protein kinase G activation by erythrocytes and conclude that erythrocytes do not release biologically active NO to inhibit platelet activation.